(untitled) (Research, Society and Development, 2021)
Damping is a property of materials that can occur on both a micro and macroscopic scale. There is a growth in the concept of analysis of structural internal crack markers that cause damage in different materials, due to its wide applicability in problem solving. In the damping process, the material loses energy when it comes into physical contact with another material, in which the phenomenon can be observed by means of modern equipment with high sensitivity under a controlled environment. There are few research institutes capable of analyzing accurate damping tests with specimens. The use of an accelerometer device circumvents the problem of the high laboratory cost involved and allows for greater accessibility. The objective is to present a methodology for analyzing parameters associated with the damping phenomenon, making use of algorithms for open access and allowing its replication in physical models. The work was efficient in determining the frequency and associated parameters of specimen signals.